Seasonal dynamics of gastrointestinal helminths in naturally infected horses in Brazil - Soutello, Ricardo Velludo Gomes de [UNESP]; Romão, Dayane Sarmento [UNESP]; do Carmo, Tábata Alves [UNESP]; de Favare, Giordani Mascoli [UNESP]; Pagnozzi, Fernanda Calazans [UNESP]; de Almeida Cipriano, Isabela [UNESP] (Elsevier, 2025)
Helminthiasis in horse breeding stands out due to the damage caused by this infection, which is mainly controlled by anthelmintic drugs. Knowing the population dynamics of helminths in a given region is therefore essential, as environmental conditions have a major impact on the development of these parasites in pastures. The aim of this study was to assess the influence of seasonality on helminths. It was carried out between October and September of the years 2015/2016, 2018/2019 and 2021/2022. A total of 147 animals were used, 64 females and 83 males, all from the same herd. Fecal samples were collected directly from the rectal ampulla of each animal every 28 days for 12 months of each cycle for coproparasitological analysis. Average air temperature, average relative humidity and rainfall were measured daily. The weather records were collected by the Agroclimatological Station in Castilho, SP (21o 05' 12.4 S; 51o 35' 17.2 W), located six kilometers from the experiment site. In the three study cycles, the EPG and rainfall averages showed significant differences between the times of year. In general, the month with the highest EPG in the different cycles was February, with 1626 in 2015/2016, 926.7 in 2018/2019 and 1885 in 2021/2022, and the month with the lowest average EPG was July, with 642 in 2015/2016, 610.5 in 2018/2019 and 804 in 2021/2022. Regarding climatic conditions, rainfall was more concentrated in two seasons, spring and summer, meaning that summer was the season with the highest rainfall in the three cycles evaluated. Autumn, followed by winter were the seasons with the lowest rainfall during the cycles studied. It can be concluded that climatic conditions have a direct influence on the population dynamics of helminths, and that during the drier and colder seasons, horses were less affected, so the suggestion for a possible strategic program would be to concentrate the administration of anthelmintics in spring and summer.
Keywords: Anthelmintic; Climate; Helminthiasis; Horses